Strikes, Wages, and Private Information - McConnell, Sheena (American Economic Review, 1989)
Private information models of strikes suggest that the strike is used as an information-revealing device by the union in the presence of asymmetrical information. A testable prediction of these models is that there is a negative relationship between strikes and the unpredicted component of the wage. This paper shows that in a large sample of U.S. labor contracts the real wage falls by about 3 percent after a strike lasting 100 days.